Effect of Deliberate Hypotension on Regional Cerebral Oxygen Saturation During Functional Endoscopic Sinus Surgery: A Randomized Controlled Trial - Zhang, Ling; Yu, Yang; Xue, Juan; Lei, Weiping; Huang, Yaqin; Li, Yong; Sun, Jianliang (Frontiers in Surgery, 2021)
Background: Deliberate hypotension can reduce bleeding and improve visualization of the surgical field during functional endoscopic sinus surgery (FESS). However, hypotension may cause brain hypoperfusion and subsequent ischemic injuries, such as delayed awakening, stroke, postoperative delirium, and postoperative cognitive dysfunction. Near-infrared spectroscopy (NIRS) can be used to monitor real-time regional cerebral oxygen saturation (rSO2) levels to estimate brain perfusion. The present study aimed to evaluate the change in rSO2 induced by deliberate hypotension during FESS, and assess the impact of deliberate hypotension on the surgical process. Material and Methods: A randomized controlled trial was registered with the Chinese clinical trial registry (ChiCTR2000039846). A total of 40 patients were enrolled and randomly divided into the control and intervention groups, and finally, 39 patients were analyzed. Deliberate hypotension was induced in the intervention group using nicardipine and esmolol, whereas the control group received general anesthesia without deliberate hypotension. We recorded mean arterial pressure (MAP), saturation of pulse oximetry (SpO2), rSO2, and heart rate (HR) before induction of anesthesia (T0), immediately after induction of anesthesia (T1), at the beginning of the operation (corresponding with the establishment of deliberate hypotension) (T2), 10 min (T3) and 20 min (T4) after the operation began, at the end of the operation (corresponding with the end of deliberate hypotension) (T5), and 5 min (T6) and 15 min (T7) after the operation. The partial pressure of end-tidal carbon dioxide (PetCO2) was recorded at T1, T2, T3, T4, T5, and T6. The duration of surgery, intraoperative blood loss, tracheal extubation time, and the number of patients that experienced cerebral desaturation events (CDEs) were recorded. The surgical field was estimated postoperation based on the Fromme score. Results: A 30% decrease from the baseline MAP resulted in a decrease of intraoperative bleeding, improvement in the quality of the surgical field, and the shortening of the duration of surgery during FESS in the intervention group compared with the control group. In addition, rSO2 was reduced and no CDEs were experienced in the intervention group. Linear regression analysis demonstrated a correlation between the decline in rSO2 and that in MAP. Conclusions: A decrease in MAP to a certain level will cause a decrease of rSO2 in patients undergoing FESS under general anesthesia. Based on our findings, we recommend that the deliberate hypotensive target indicated by MAP be reduced by 30%, while PetCO2 is maintained at 35–40 mmHg and HR is maintained at about 60 beats per minute during FESS.